Estimating potential saving with energy consumption behaviour model in higher education institutions - Ishak, M. H. (Chinese Institute of Environmental Engineering, 2016)
Towards sustainable Higher Education Institutions (HEIs), energy consumption behaviour is one of several issues that require an attention by facilities manager. Information from the behavioural aspect would be useful for facilities manager on managing the energy and determining potential energy saving. A lack of information negatively affects this aim. Hence, this paper proposes a methodology for assessing the energy consumption behaviour with the objective determining potential energy saving. The method used energy culture framework as basis and joined with centrographic approach and multiple-regression analysis. A self-administrated survey carried out involving 1400 respondents in selected HEIs. There are four types of energy use among students in HEIs namely, ‘high’, ‘low’, ‘medium’ and ‘conserve’ determined from the centrographic analysis. The energy consumption behaviour model was developed and tested against the holdout sample. Through the model's application, there is a vast potential for energy savings with over 55 kWh daily among the students.